The Design of Audio Delay Module to Create - Hans Kristanto; Sutrisno . (Institute of Research and Community Outreach, Petra Christian University, 2016)
Humans have the ability to determine the location of a sound source using two ears as a comparison called sound localization, just like the eyes when viewing a 3D movie. In the car, there are two sources of sound that left and right speakers. Both of these sound sources can lead to the creation of staging and imaging effects. However, unlike the home multimedia system that can be placed symmetrically to the listener. Therefore, the device needs to set the delivery time of the sound by the speaker. This research is done by designing a module to determine the accuracy of the module is carried out experiments using two different power supply. Power supply is contained in the adapter laboratory control system and the battery 9 V. From the research conducted, it was found that there was a difference delay generated IC PT2399 when it gets electricity from the power supply source is different. In this study also found that the time difference of the sound of each speaker to the ear affects the quality of staging and imaging effects, audio systems that use delay has a staging location in front of the driver.